Antibacterial activity of Cordia dentata Poir, Heliotropium indicum Linn and Momordica charantia Linn from the Northern Colombian Coast (2017)
Cordia dendata Poir, Heliotropium indicum Linn and Momordica charantia Linn areused for treatment of the most common human diseases and health disorders in folkmedicine of the population from the northern Colombian coast. In this study, chemicalcomposition and antibacterial activity of the ethanol extract and fractions fromC. dentata, H. indicum and M. charantia were investigated. The chemical constituentsof qualitative detection were examined by Thin Layer Chromatography (TLC).The antibacterial activity was determined by agar gel diffusion and broth microdilutionmethod. The main identified compounds were flavonoids, cardiac glycosides,alkaloids, saponins, terpenoids, tannins and coumarins. The minimal inhibitoryconcentration (MIC) was 31.25 to 1000 g/mL for Gram-positive and Gram-negativebacteria, respectively. These results indicated that ethanol extract and fractionsfrom C. dentata, H. indicum and M. charantia significantly inhibited the growthof standard strains. Potent antibacterial activities of C. dentata, H. indicum and M.charantia may be considered in future study, particularly against antibiotic-resistantcases.